Strategi Pembelajaran Tahfidz Al-Qur’an Di Pondok Pesantren Tahfidzul Qur’an Baitul Abidin Darussalam Wonosobo - M. Nazilul Furkon; Ahmad Zuhdi; Ngatoillah Linnaja (STIKes Ibnu Sina Ajibarang, 2024)
Baitul Abidin Darussalam Tahfidzul Qur'an Islamic Boarding School is an Islamic boarding school based on Al-Qur'an tahfidz which is located in Sarimulyo Hamlet, Rt 01 Rw 10 Kalibeber Village, Mojotengah District, Wonosobo Regency. The Baitul Abidin Darussalam Tahfidzul Qur'an Islamic Boarding School is adjacent to other Al-Qur'an Tahfidz Islamic Boarding Schools in Kalibeber Village, one of which is the Al-Asy'ariyyah Tahfidzul Qur'an Islamic Boarding School. However, the Al-Qur'an learning strategy at the Tahfidzul Qur'an Islamic Boarding School is very different from other Islamic boarding schools which are both based on the Al-Qur'an. This research aims to determine the tahfidz Al-Qur'an learning strategy used by the Baitul Abidin Darussalam Wonosobo Tahfidzul Qur'an Islamic Boarding School in teaching and training students to memorize the Al-Qur'an in its entirety. The method used in this research is to use a qualitative research methodology with a descriptive approach, namely by using research that produces descriptive data in the form of written or spoken words. Data collection techniques use observation, interviews and documentation methods. The data analysis technique goes through three stages, namely data reduction, data display, and verification. The research results show that the tahfidz Al-Qur'an learning strategy implemented at the Tahfidzul Qur'an Islamic Boarding School uses 3 strategies, namely, First, using a preparation strategy, a double repetition strategy, and a retention strategy.